Aljamiado Literature in Renaissance Europe. Definitions, Area, Language - de Castilla, Nuria; Kulwicka-Kamińska, Joanna; Cychnerska, Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
Literature written in the local language adapted to the Arabic alphabet and developed under strong influences of Islamic tradition and culture is referred to as aljamiado literature. It is not limited to a specific language or a particular adaptation of the Arabic alphabet for non-Arabic languages. In this article, aljamiado literature encompasses writings primarily of religious nature, created on the Iberian Peninsula, in the Balkans, and in the former Grand Duchy of Lithuania, which includes present-day Lithuania, Belarus, parts of Poland, and Ukraine. The presented research has a pioneering character, focusing on the specificity of aljamiado creativity in selected European countries historically influenced by the Ottoman Empire. It emphasises the similarities resulting from the connection with Islam, as well as the differences stemming from historical and geographical factors.